THE IMPACT OF CAREER PLATEAUS ON EMPLOYEE JOB SATISFACTION. THE MODERATING ROLE OF REMOTE WORK - Bareja-Wawryszuk, Ola; Togonidze, Vladimer; Aslantas, Mirac (Management and Administration Journal, 2025)
This study examines the impact of career plateaus on job satisfaction, highlighting the moderating role of remote work. Career plateau, characterized by limited career advancement opportunities, has been identified as a significant detractor of employee engagement and satisfaction. Leveraging the flexibility and autonomy of remote work, this research explores its potential to mitigate the adverse effects of career stagnation. A quantitative methodology was applied, analyzing survey data from public and private sector employees in Georgia using linear regression to test the hypotheses. The findings confirm a negative correlation between career plateau and job satisfaction, while greater autonomy in remote work significantly enhances job satisfaction levels. The study underscores the necessity of implementing job-design strategies that incorporate flexible employment forms as a means to counteract the effects of career stagnation and promote employee well-being.